PROPERTIES OF COMPLEX COMPOUNDS OF S-ELEMENTS - Ospanova Zukhra Sarsenbaevna; Sarsenbaev Ilhambay Eliwbay o’g’li (Western European Studies, 2024)
The chemistry of the S elements of groups I and II is mainly related to the chemistry of the ions, with the exception of lithium and beryllium. The small size of the cations of these two elements makes them very polar, so the chemistry of beryllium can be considered fully covalent and the chemistry of lithium can be considered partially covalent. The ionic radius is the main factor that determines the coordination number of the cation, its degree of hydration and, therefore, the solubility of salts. Cations of the main subgroup elements of Group I usually form unstable complexes with oxygen donors. However, there are ammonias that are very unstable but can persist for a long time under certain conditions.
Keywords: kompleks; ligand; markaziy; ion